Polymorphisms in Fc Gamma Receptors and Susceptibility to Malaria in an Endemic Population - Amiah, Mireille Ahou; Ouattara, Amed; Okou, David Tea; N’Guetta, Simon-Pierre Assanvo; Yavo, William (Frontiers in Immunology, 2020)
Repeated infections by Plasmodium falciparum result in a humoral response that could reduce disease symptoms and prevent the development of clinical malaria. The principal mechanism underlying this humoral response is that immunoglobulin G (IgG) binds directly to the parasites, thus causing their neutralization. However, the action of antibodies alone is not always sufficient to eliminate pathogens from an organism. One key element involved in the recognition of IgG that plays a crucial role in the destruction of the parasites responsible for spreading malaria is the family of Fc gamma receptors. These receptors are expressed on the surface of immune cells. Several polymorphisms have been detected in the genes encoding these receptors, associated with susceptibility or resistance to malaria in different populations. In this review, we describe identified polymorphisms within the family of Fc gamma receptors and the impact of these variations on the response of a host to infection as well as provide new perspectives for the design of an effective vaccine for malaria.